Splenectomy for treating hepatosplenic candidiasis: Two cases and literature review suggesting its feasibility - Songfeng Yu; Yanling Ren; Xue Wen; Yufu Ye; Longyu Cheng; Jun Yu; Shusen Zheng (Heliyon, 2023)
Background: Hepatosplenic candidiasis is a rare but severe complication in immunocompromised patients undergoing chemotherapy. Antifungal agents are widely accepted as the first choices for therapy. However, resistance to or side-effect of antifungal agents may comxpromise its efficiency. Splenectomy has also been rarely performed as treatment for this disease. Methods: We present two cases of splenectomy for treating hepatosplenic candidiasis after failure of the initial drug therapy. Literatures on splenectomy as treatment for hepatosplenic candidiasis were searched in Pubmed and summarized. Results: Two leukemia patients developed hepatosplenic candidiasis after received chemotherapy for their primary diseases. Various antifungal agents including amphotericin B were all demonstrated failure to cure fever and the Candida abscesses due to resistance or intractable side-effect. Laparoscopic splenectomy were finally performed and resolved the candidiasis successfully. A total of 12 splenectomy cases for treating hepatosplenic candidiasis had been previously reported in literature. All the cases showed either resistance or unimproved to initial antifungal therapies. Splenectomy provided salvage therapeutic value in all cases. Conclusion: Splenectomy has therapeutic effect and may change the traditional concept in most surgeons. The present study may expand an alternative strategy in clinical practice guideline for the management of hepatosplenic candidiasis.